The Role of Postoperative Radiotherapy for Large Nerve Perineural Spread of Cancer of the Head and Neck - Gorayski, Peter; Foote, Matthew; Porceddu, Sandro; Poulsen, Michael (Journal of Neurological Surgery Part B: Skull Base, 2016)
Large nerve perineural spread (LNPNS) is an uncommon but serious sequelae of cutaneous and salivary gland malignancies arising in the head and neck. This distinct clinical entity is caused by malignant cell spread along the course of larger (named) cranial nerves in a bidirectional pattern of spread toward the origins of the nerve in the brainstem and/or its most distal branches residing in the dermis. Untreated, LNPNS causes multiple cranial neuropathies that significantly impact on quality of life and ultimately is fatal. Curative treatment involves en bloc surgical resection of all known involved sites of gross disease followed by risk-adapted postoperative radiotherapy (PORT) to improve local control. We review the evidence for contemporary practice and outline the processes involved in the delivery of PORT using the zonal anatomical classification.
Keywords: perineural infiltration; radiotherapy; cutaneous; skull base; squamous cell carcinoma; adenoid cystic carcinoma